PENGARUH MINAT BELAJAR DAN LINGKUNGAN TEMAN SEBAYA TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPS KELAS VII SMP NEGERI 5 PEMATANGSIANTAR - Lasio Loy Della Simanjuntak; Injen Pardamean Butarbutar; Benjamin Albert Simamora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of learning interest and peer environment on students’ learning outcomes in Social Studies subjects for seventh grade students at SMP Negeri 5 Pematangsiantar. The background of this study is based on the low student learning outcomes, as indicated by the large number of students who have not achieved the Learning Objective Achievement Criteria (KKTP). The factors assumed to influence learning outcomes in this study are learning interest and peer environment. This study used a quantitative method with an explanatory survey approach. The population in this study consisted of all seventh grade students at SMP Negeri 5 Pematangsiantar, totaling 158 students. The sampling technique used was proportionate stratified random sampling, resulting in a sample of 113 students. Data were collected through questionnaires and documentation. The research instruments were tested using validity and reliability tests. The data analysis techniques included classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination test (R²). The results of the study showed that: (1) learning interest had a positive and significant influence on students’ learning outcomes, proven by a significance value of 0.000 < 0.05 and a t-value of 7.489; (2) peer environment had a positive and significant influence on students’ learning outcomes, proven by a significance value of 0.000 < 0.05 and a t-value of 4.371; and (3) learning interest and peer environment simultaneously had a positive and significant influence on students’ learning outcomes, proven by a significance value of 0.000 < 0.05 and an F-value of 72.040. The coefficient of determination test (R²) showed a value of 0.567 or 56.7%, which means that learning interest and peer environment contributed 56.7% to students’ learning outcomes, while the remaining 43.3% was influenced by other factors outside this study. Based on the results of the study, it can be concluded that learning interest and peer environment have a positive and significant influence on students’ learning outcomes in Social Studies subjects for seventh grade students at SMP Negeri 5 Pematangsiantar in the 2025/2026 Academic Year.